Neue Grabinschriften aus Neoklaudiopolis (Vezirköprü/Samsun İli, Türkei) - Vera SAUER (Akdeniz University, 2021)
Up to now, about 140 funerary inscriptions were known from the territory of Neoklaudiopolis/Vezirköprü. In this contribution, 14 more are presented, one of which, however, may be attributed to Amaseia/Amasya (no. 4). They were recorded between 1988 and 1990 by Eckart Olshausen and Gerhard Kahl. All of them date back to the Roman Imperial period. One of the stelae stands out for its unusually high-quality stone carving (no. 8); it was erected by a veteran for his wife. Three other stelae are either composed in a way unusual for Neoklaudiopolis or contain decorative elements, which, until now, are not attested for grave stelae from the territory of this polis: at nos. 1 and 2 a depictive field was inserted between the pediment and the inscription field being separated from the latter by a moulding, at no. 4 a garland is placed above the inscription. Two of the inscriptions use metric language (nos. 4 and 9). Some of them contain rarely attested personal names (nos. 1, 2, 7, 9, 12 and 14). Age information is found in at least two (nos. 10 and 11, possibly also in no. 12). No. 2 and no. 13 are particularly interesting in terms of content. No. 2 mirrors the fate of a man and his mother. In no. 13, the donor of the stele explicitly refers to his deceased wife as his relative – for whatever reason. Finally, in the light of inscriptions nos. 13 and 14, we discuss an inscription published by Christian Marek in an appendix.